Reliability of information systems in organization in the context of banking sector: Empirical study from Poland - Katarzyna Tworek (Cogent Business & Management, 2018)
The notion of information systems (IS) reliability in organization is discussed in this article. It contains critical review of the literature, definition of IS reliability and brief overview of the theoretical model of IS reliability in organization developed by the author (including system reliability, information reliability, service reliability and usage reliability). The potential use of the model of IS reliability is demonstrated as a part of empirical research devoted to the analysis and evaluation of IS by the information technology (IT) specialists from inside and outside of the banking sector. The analysis is based on survey conducted among more than 200 IT specialists from and outside of the banking sector in Wroclaw, Lower Silesia, Poland. Banking sector is given as an example due to its uniqueness—extreme sensitivity to IS reliability and accuracy. The analysis of IS reliability in organization is supplemented by the comparison of the way of understanding the notion by the two groups of specialists in order to verify whether the IS reliability is understood in the same way by industry sectors differing in terms of their sensitivity to IS support.
Keywords: 650